Current Status and Perspectives on the Use of Traditional Chinese Medicine in the Treatment of Gastric Cancer - Hu, Yonghua; Yang, Lei; Tong, Jianning; Li, Haiyuan; Wei, Qinglin; Chen, Hao (Current topics in nutraceuticals research, 2024)
In recent years, the potential of Traditional Chinese Medicine in preventing and treating gastric cancer has gained clear recognition. However, there is a lack of comprehensive analysis of the data on the involvement of Traditional Chinese Medicine in the prevention, diagnosis, and treatment of gastric cancer. Therefore, this article aims to organize and analyze relevant information to provide a reference for the use of Traditional Chinese Medicine in the prevention and treatment of gastric cancer.